Using hybrid of block-pulse functions and bernoulli polynomials to solve fractional fredholm-volterra integro-differential equations - Saadatmandi, Abbas; Akhlaghi, Samiye (Penerbit Universiti Kebangsaan Malaysia, 2020)
Fractional integro-differential equations have been the subject of significant interest in science and engineering problems. This paper deals with the numerical solution of classes of fractional Fredholm-Volterra integro-differential equations. The fractional derivative is described in the Caputo sense. We consider a hybrid of block-pulse functions and Bernoulli polynomials to approximate functions. The fractional integral operator for these hybrid functions together with the Legendre-Gauss quadrature is used to reduce the computation of the solution of the problem to a system of algebraic equations. Several examples are given to show the validity and applicability of the proposed computational procedure.